2014
DOI: 10.1159/000363479
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Monitoring: Professional and Real Time

Abstract: Continuous glucose monitors are a valuable tool to obtain tight glycemic control in people with diabetes. Since 1999 when the first continuous glucose monitor became commercially available, continuous glucose monitors have continued to evolve, becoming more accurate and user-friendly. Novel uses have also been discovered, including tracking glucose during sleep and finding trends in glucose levels that may lead to diet or exercise changes. While continuous glucose monitors are continually advancing in accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…One example of wearable biosensors with the potential to be used in behavioral research is the continuous glucose monitor (CGM). The CGM measures the concentration of glucose subcutaneously (interstitial fluid) in real time through a tiny sensor inserted under the skin [ 10 ]. It has been primarily utilized by type 1 diabetic patients treated by intensive insulin therapy to make treatment decisions that promote glycemic control [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…One example of wearable biosensors with the potential to be used in behavioral research is the continuous glucose monitor (CGM). The CGM measures the concentration of glucose subcutaneously (interstitial fluid) in real time through a tiny sensor inserted under the skin [ 10 ]. It has been primarily utilized by type 1 diabetic patients treated by intensive insulin therapy to make treatment decisions that promote glycemic control [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This has been further endorsed by the fact that CE (Conformite Europeenne) and US FDA have approved some CGM devices for adjustment of insulin dosages [ Figure 15 ]. [ 750 751 752 ] CGMs broadly fall into two categories. The 'Professional CGM' (P-CGM), meant for the healthcare professionals to record the patient's ambulatory glucose values, which are then downloaded and used for retrospective review and analysis.…”
Section: R Ationale and E Videncementioning
confidence: 99%
“…These systems collect glucose data and store it in a hospital information system, which makes it possible for medical staff to access real-time data from their patients [19]. Since the first CGM was presented and made available in 1999, several continuous glucose monitors have continued to evolve to become more accurate and user-friendly [20]. Statistics have demonstrated that CGM may reduce patient's long-term complications between 40% and 75% of the time [20].…”
Section: Continuous Glucose Monitoringmentioning
confidence: 99%
“…Since the first CGM was presented and made available in 1999, several continuous glucose monitors have continued to evolve to become more accurate and user-friendly [20]. Statistics have demonstrated that CGM may reduce patient's long-term complications between 40% and 75% of the time [20]. The CGM can also be equipped with an alarm system, which may help the patient to take the correct actions when it comes to their diet, physical experience and remind them when it is time to take their medications [19].…”
Section: Continuous Glucose Monitoringmentioning
confidence: 99%